Treatment with Terminalia chebula (retz.): possible mechanism of inhibition of spermatogenesis and fertility in albino mice - Gupta, Prakash Chandra; Yadav, Laxmi (Journal of Applied Pharmaceutical Research, 2024)
Background: There has been a continued effort to develop an effective male contraceptive of plant origin due to its ready availability, cost-effectiveness, and fewer side effects.  The present study has evaluated the mechanism of inhibitory action of Terminalia chebula Retz. (T. chebula; family: Combretaceae) on spermatogenesis and fertility in albino mice after oral administration of the aqueous bark extract (100, 300, and 500 mg/kg BW daily) of T. chebula for 35 d. Methodology: The effects of the Terminalia treatment on various reproductive endpoints such as sperm parameters, testis histology, activities of 3ß- and 17ß-HSDs, immunoblot expressions of StAR and AR proteins, immunostaining of AR, serum testosterone level, LPO level, activities of SOD and catalase, and fertility indices were investigated. Toxicological and recovery studies have also been performed. Results: Testes in Terminalia-treated mice showed nonuniform histologic alterations. Sperm parameters, activities of 3ß- and 17ß-HSDs, immunoblot expressions of StAR and AR proteins, immunostaining of AR, and serum testosterone level were adversely affected, though activities of SOD and catalase were unchanged. Libido remained unaffected, but fertility was inhibited markedly in treated males without signs of toxicity. By 42 d of treatment discontinuation, Terminalia-induced deviations in the reproductive endpoints recovered to control levels. Conclusion: The results of the present study indicate that T. chebula treatment reversibly inhibits spermatogenesis and fertility without signs of toxicity. Further, antifertility effects result from diminished production of testosterone due to Terminalia-mediated inhibition of testicular steroidogenesis.